A Case of Intrapancreatic Accessory Spleen Mimicking a Pancreatic Metastasis on the 18F-FDG PET/CT Scan: A Case with Breast Cancer - Yildirim, Mustafa; Artas, Hakan (Thieme Medical Publ Inc, 2021)
The accessory spleen is a focus of splenic tissue which is separated from the main of the spleen. Although accessory spleens are generally recognized on computed tomography (CT), intrapancreatic accessory spleen (IPAS) may be mistaken for other pancreatic tail lesions. We report a case of IPAS mimicking a pancreatic metastasis on the F-18-fluorodeoxyglucose positron emission tomography/computed tomography (F-18-FDG PET/CT). A 41-year-old with diagnosed breast cancer (invasive ductal carcinoma) woman patient underwent an F-18-FDG PET/CT for metastasis screening and staging. F-18-FDG PET/CT showed a focal uptake in the pancreatic tail. The patient underwent a contrast-enhanced CT and magnetic resonance imaging (MRI) for lesion characterization. The density and intensity of lesion were similar to spleen on all phases and all sequences. The lesion was evaluated as IPAS. The diagnosis was confirmed by endoscopic ultrasound (EUS) biopsy. A case of IPAS positive at F-18-FDG PET/CT could not found in the literature. We present a case of IPAS mimicking a pancreatic metastasis positive at F-18-FDG PET/CT.
Keywords: Intrapancreatic accessory spleen; FDG PET/CT; Pancreatic metastasis